The subject of endowment properties in Algeria to the provisions of French real estate transactions from 1844 -1897 - mezoudji, hichem; Himeur, salah (The Algerian Historical Journal, 2026)
The issue of Algerian endowments during the French colonial era is one of the most important topics that still need further research, and the aim of this topic is to identify how endowment properties in Algeria are subject to the provisions of French real estate transactions from 1844 to 1897. As for the results of this study, the French colonial administration was able to subject the various endowment properties to the French real estate laws, thus Frenchizing the Algerian endowments and getting rid of the legitimacy of endowments that derive their provisions from Islamic law, introducing them into the real estate trade exchange and facilitating the process of their transfer from Algerians to Europeans.